REVIEW : PENGEMBANGAN SISTEM PENGHANTARAN BERBASIS NANOPARTIKEL DALAM SEDIAAN KOSMESETIKA HERBAL - Risa Ahdyani; Sri Rahayu; Irfan Zamzani; Andika Andika (JCPS (Journal of Current Pharmaceutical Sciences), 2020)
Herbal cosmeceuticals are cosmetic-pharmaceutical hybrids intended to enhance health and beauty through natural ingredients that are applied onto skin surface. The ability of an ingredient in enhancing skin's biological texture and function depends on the delivery system to reach specific targeted sites in an amount sufficient to exert an effect in a controlled manner. The novel approach that could be used in the delivery of herbal cosmeceuticals is nanoparticle-based delivery system. Many researches have been conducted on the development of nanoparticle-based delivery system containing natural ingredients such as gotu kala extract, rosemary extract, orange peel extract, ginseng extract, basil extract, safflower extract, resveratrol, and Taduvelai extract. Based on the literature study of previous researches reported that nanoparticle-based delivery system has been successfully delivered those natural ingredients through certain mechanism in enhancing activity as skin antiaging, skin whitening, antiacne, and hair care product.